Penggunaan Bahasa Mandarin Dalam Dakwah Oleh Gerakan-Gerakan Dakwah: Sumbangan dan Peranannya di Malaysia - Nur Aisyah Abu Hassan; Safinah Ismail; Aemy Elyani Mat Zain; Siti Zahidah Mual (Wardah, 2019)
Abstract: Delivering da’wah by using the foreign language is one of the new approaches in da’wah strategy. Some of the preachers aware on it and indirectly involved in this kind of da’wah by using Mandarin language. That is why the are several of da’wah associations like PERKIM, YADIM and MACMA use the language of Mandarin in da’wah. Hence, the purpose of the paper is to discuss the using of Mandarin language among some of da’wah associations by concentrating their contributions dan their roles in presenting da’wah in Malaysia. Keywords: Mandarin, da’wah association, MACAM, YADIM, PERKIM